1975
DOI: 10.1039/p29750000938
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 nuclear magnetic resonance spectra of some polyphosphines with ethane bridges between trivalent phosphorus atoms

Abstract: H and C6H5), and P(CH,CH,PH,), have been examined. Replacement of alkyls by hydrogen in R, P units consistently raises the 13C n.m.r. chemical shifts (i.e., lowers the 6 values) of CH, groups attached to this phosphorus. The spin-spin splittings in the 13C n.m.r. spectra by the phosphorus atoms in (C6H5)2PCH2CH,P(C6H5), and C6H5P[CH,CHzP-,], must be analysed as second-order ABX systems whereas those in the remaining polyphosphines can be analysed as first-order AMX systems. The range of significant phosphorus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…In general, carbonyl complexes of iron (Fe(CO) 5 , Fe 2 (CO) 9 and Fe 3 (CO) 12 ) react with monodentate phosphine ligands to give mixtures of the mono-and disubstituted derivatives [Fe(CO) 4 L] and [Fe(CO) 3 L 2 ] [48,49]. This behaviour is expected to result from the intermediary [Fe(CO) 4 ] [50,51].…”
Section: Preparation Of the Rumentioning
confidence: 94%
See 2 more Smart Citations
“…In general, carbonyl complexes of iron (Fe(CO) 5 , Fe 2 (CO) 9 and Fe 3 (CO) 12 ) react with monodentate phosphine ligands to give mixtures of the mono-and disubstituted derivatives [Fe(CO) 4 L] and [Fe(CO) 3 L 2 ] [48,49]. This behaviour is expected to result from the intermediary [Fe(CO) 4 ] [50,51].…”
Section: Preparation Of the Rumentioning
confidence: 94%
“…The polyphosphines containing terminal alkoxy groups provide chelating ligands with stronger p-accepting properties than polyphosphines containing terminal alkyl groups [2][3][4], owing to the greater electronegativity of the alkoxy substituents [5]. Essentially two methods have been applied to introduce alkoxy substituents on a phosphorus atom: the alcoholysis of aminophosphine derivatives [6][7][8][9][10] or the reaction of chlorophosphine derivatives with an alcohol in the presence of a tertiary amine base [11][12][13][14][15].…”
Section: Preparation Of the Tridentate Phosphine Ligands I-ivmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, in Ref. 20 dealt with the study of polyphosphines with the ethylene bridge, it has been reported that the signals for the 13 C carbon atoms of the PCH 2 CH 2 P group are triplets and this was the basis for the suggestion on the equivalence of the 1 J C,P and 2 J C,P spin spin coupling constant values in such a fragment. Taking into account the complex char acter of the multiplets observed in the 13 C NMR spectra, we simulated the 13 C NMR spectrum using the gNMR 5.0 program, which allows one to perform the iteration selec tion of spectral parameters (Fig.…”
mentioning
confidence: 96%
“…Simulation of the variable temperature 11 3 Cd NMR spectra yielded another set of rate constants (see Figure 2) as a function of temperature which were comparison, the 3-bond P-P coupling constant for the heterobimetallic compound through the P-CH 2 CH 2 -P' chain is similar to the value reported for R 2 PCH 2 CH 2 PR' 2 species where R and R' are different. 43 46 The presence of the 3-bond P-P coupling is consistent The structural integrity of the mixed metal species, 7 was investigated in the solid state by X-ray powder diffraction. The X-ray powder diffraction data for the heterobimetallic species 7 did not match that of either the homobimetallic species 5 or 6.…”
Section: Introductionmentioning
confidence: 99%